Effect of weather variables on the incidence of yellow stem borer (Scirpophaga incertulas W.) and leaf folder (Cnaphalocrocis medinalis G.) in rice - Jasrotia, Poonam; Khippal, Anil; Yadav, Jayant; Kashyap, Prem Lal; Kumar, Sudheer; Singh, Gyanendra Pratap (Journal of Cereal Research, 2019)
A study was conducted on rice variety CSR 30 to analyse the impact of abiotic factors on yellow stem borer, Scirpophaga incertulas (Walker) and leaf folder, Cnaphalocrocis medinalis (Guenee) infestation during Kharif season of 2016 and 2017 at Research Farm, Indian Institute of Wheat and Barley Research, Karnal, Haryana. The infestation of yellow stem borer and leaf folder was noticed in the field from 45th SMW during both years of investigation. The maximum damage of 14.9% and14.5% by yellow stem borer was recorded during 38th SMW in 2016 and during 39th SMW in 2017, respectively.The damage by leaf folder attained peak during 3rd week of September (38th SMW) during 2016 and 2017 with 8.4% and 9.7% infestation levels, respectively. Yellow stem borer infestation exhibited significant negative correlation with morning relative humidity (r = -0.506), evening relative humidity (r = -0.620) and rainfall (r = -0.481). The correlation of incidence of leaf folder damage was found to be significantly positive with maximum (r = 0.619) and minimum temperature (r = 0.552). Other weather parameters showed a non-significant positive and negative relationship with the yellow stem borer and leaf folder population. The studies indicated the role of weather parameters on the abundance of yellow stem borer and leaf folder infestation in rice.DOI:https://doi.org/10.25174/2249-4065/2019/95416